2018
DOI: 10.1080/13607863.2018.1450835
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and social isolation among older adults in a community exercise program: a qualitative study

Abstract: This study provides insight into participants' experiences of L&SI. Further research in a broader population of older adults is mandated to determine the efficacy of community exercise programs in reducing L&SI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 32 publications
0
44
0
Order By: Relevance
“…Included papers in the present review, also indicate that community-based programs have the potential to decrease feelings of isolation [45]. In the situation of home-confinement, exergames are a perfect innovation which should have the integrated function of a group-play modus [53].…”
Section: Practical Recommendationsmentioning
confidence: 81%
“…Included papers in the present review, also indicate that community-based programs have the potential to decrease feelings of isolation [45]. In the situation of home-confinement, exergames are a perfect innovation which should have the integrated function of a group-play modus [53].…”
Section: Practical Recommendationsmentioning
confidence: 81%
“…The social interaction provided by group-based exercise programs proved beneficial for older adults to overcome psychosocial conditions, such as loneliness, depression, and low self-esteem [46]. Moreover, studies showed that there is a strong correlation between the use of exergames and positive mood among older adults living independently [47].…”
Section: Discussionmentioning
confidence: 99%
“…They found significant changes in happiness, loneliness, life satisfaction and depression in the exercise group. A recent qualitative research revealed that older adults participating in a community-based program of socialization, health education exercise and walking reduced their feelings of loneliness and social isolation [46].…”
Section: Discussionmentioning
confidence: 99%